Sobreinfección por Pneumocystis jirovecii y Staphylococcus aureus resistente a meticilina tras infección por SARS-CoV2. - Marta Olimpia Lago Rodríguez; Crhistian Mario Amodeo Oblitas; Carmen Cuenca Carvajal (Sociedade Galega de Medicina Interna, 2022)
We present a case of an 87-year-old nonsmoker female who recovered after infection by SARS-CoV2 and was readmitted two weeks later due to respiratory sepsis. Radiological imaging showed a significant radiological worsening with extensive areas of bronchopneumonia and ground-glass opacities suggestive of organizing pneumonia. Empirical treatment with meropenem 1g/8h was started; however, clinical worsening persisted with tachypnea and desaturation requiring heated high-flow nasal cannula oxygen therapy, with poor response. Methicillin-resistant Staphylococcus aureus was isolated both in nare screening and sputum, and 16S rRNA polymerase chain reaction in induced sputum was positive for P. jirovecii. Serum (1-3)-beta-D-glucan was normal, and blood cultures were sterile. Antibiotic therapy was adjusted with intravenous linezolid 600mg/12h and trimethoprim-sulfamethoxazole 1600/320mg/6h, plus methylprednisolone 40mg/day. Unfortunately, the patient had no response to optimized treatment and finally died. Opportunistic and resistant microorganisms superinfections should be aware by clinicians in SARS-CoV2 infection, even more, when corticosteroids are widely used.